Salt stress proteins in plants: An overview - Athar, Habib-ur-Rehman; Zulfiqar, Faisal; Moosa, Anam; Ashraf, Muhammad; Zafar, Zafar Ullah; Zhang, Lixin; Ahmed, Nadeem; Kalaji, Hazem M.; Nafees, Muhammad; Hossain, Mohammad Anwar; Islam, Mohammad Sohidul; El Sabagh, Ayman; et al. (Frontiers in Plant Science, 2022)
Salinity stress is considered the most devastating abiotic stress for crop productivity. Accumulating different types of soluble proteins has evolved as a vital strategy that plays a central regulatory role in the growth and development of plants subjected to salt stress. In the last two decades, efforts have been undertaken to critically examine the genome structure and functions of the transcriptome in plants subjected to salinity stress. Although genomics and transcriptomics studies indicate physiological and biochemical alterations in plants, it do not reflect changes in the amount and type of proteins corresponding to gene expression at the transcriptome level. In addition, proteins are a more reliable determinant of salt tolerance than simple gene expression as they play major roles in shaping physiological traits in salt-tolerant phenotypes. However, little information is available on salt stress-responsive proteins and their possible modes of action in conferring salinity stress tolerance. In addition, a complete proteome profile under normal or stress conditions has not been established yet for any model plant species. Similarly, a complete set of low abundant and key stress regulatory proteins in plants has not been identified. Furthermore, insufficient information on post-translational modifications in salt stress regulatory proteins is available. Therefore, in recent past, studies focused on exploring changes in protein expression under salt stress, which will complement genomic, transcriptomic, and physiological studies in understanding mechanism of salt tolerance in plants. This review focused on recent studies on proteome profiling in plants subjected to salinity stress, and provide synthesis of updated literature about how salinity regulates various salt stress proteins involved in the plant salt tolerance mechanism. This review also highlights the recent reports on regulation of salt stress proteins using transgenic approaches with enhanced salt stress tolerance in crops.